2022
DOI: 10.1101/2022.02.16.480765
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Genetic and Evolutionary Basis of Gene Expression Variation in East Africans

Abstract: Background: Mapping of quantitative trait loci (QTL) associated with molecular phenotypes is a powerful approach for identifying the genes and molecular mechanisms underlying human traits and diseases. How the genetic architecture of molecular traits varies across human populations, however, has been less explored. To better understand the genetics of gene regulation in East Africans, we perform expression and splicing QTL mapping in whole blood from a cohort of 162 diverse Africans from Ethiopia and Tanzania.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 101 publications
(149 reference statements)
0
3
0
Order By: Relevance
“…In spite of our limited sample size, these findings suggest a distinctive and distinguishable (relative to previously characterized European data) Indonesian sQTL signal, as we would expect sharing between GTEx and BLUEPRINT to also be negatively impacted by the relatively low sample size in BLUEPRINT and their distinct processing pipelines. By profiling the differences and similarities across these groups, we can more accurately characterize the gene regulatory mechanisms underlying diversity in genetic traits, highlighting the value of trans-ethnic, trans-environment QTL mapping to maximize discovery of gene regulatory variation across humans [30,32].…”
Section: Characterisation Of Indonesian Cis-sqtls In Whole Bloodmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of our limited sample size, these findings suggest a distinctive and distinguishable (relative to previously characterized European data) Indonesian sQTL signal, as we would expect sharing between GTEx and BLUEPRINT to also be negatively impacted by the relatively low sample size in BLUEPRINT and their distinct processing pipelines. By profiling the differences and similarities across these groups, we can more accurately characterize the gene regulatory mechanisms underlying diversity in genetic traits, highlighting the value of trans-ethnic, trans-environment QTL mapping to maximize discovery of gene regulatory variation across humans [30,32].…”
Section: Characterisation Of Indonesian Cis-sqtls In Whole Bloodmentioning
confidence: 99%
“…A study of the response to infection in monocytes from individuals of European and African descent living in Belgium showed that genetic ancestry consistently contributed to differences in splicing, and highlighted the role of archaic introgression from Neanderthals [21] in particular. Recently, a separate study examining both expression and splicing in whole blood in East African populations has shown that overall, the genetic architecture of splicing is shared between individuals of African and European ancestry, but nonetheless identified a substantial number of sQTLs in individuals from Tanzania and Ethiopia that have not been reported in European cohorts [32].…”
Section: Introductionmentioning
confidence: 99%
“…Only 112,316 of the 354,931 (31.64%) eSNPs in African Americans were also identified in European Americans. The latest eQTL research using 162 East African whole blood samples by Kelly et al 80 identified 99,685 SNPs associated with 1,330 eGenes. Ninety-eight of 1,330 eGenes were not found in the GTEx eQTL database.…”
Section: Eqtl Studies In Historically Excluded Populationsmentioning
confidence: 99%